USING LANGUAGE EXPERIENCE APPROACH THROUGH DIGITAL MEDIA TO PROMOTE ENGLISH READING AND WRITING ABILITIES AND MEDIA LITERACY OF GRADE 12 STUDENTS - Porjor, Sarawut; Assapaporn, Natad (Journal of Education and Innovation, 2024)
The objectives of this research were to 1) create and find the quality of the lesson plans using language experience approach through digital media to promote English reading and writing abilities and media literacy, 2) compare English reading abilities, 3) compare English writing abilities before and after studying with language experience approach through digital media, and 4) examine media literacy of students after studying with language experience approach through digital media. The target group was 26 students in Doi Tao Wittayakom School, Chiang Mai, selected by cluster random sampling. The research instruments were an evaluation form of lesson plans quality, test for reading abilities (20 items), test for writing abilities (2 items), and form of media literacy scale (25 items). The data were analyzed by using means, standard deviations, percentages and quality of English reading ability based on the criteria. The results showed that: 1) there were 7 lesson plans (3 hours per each, altogether 21 hours) using language experience approach through digital media to promote English reading and writing abilities and media literacy which had very good quality; 2) the English reading abilities; 3) the English writing abilities after studying was higher than before studying with language experience approach through digital media; and 4) the media literacy of students after studying with language experience approach through digital media had high level.